Operational risk, omissions and liability in policing. (June 2019) - Heaton, Robert; Bryant, Robin; Tong, Stephen
Recent decades have seen the sensitisation of UK society towards harm and policing 'failures' become increasingly significant. This paper is intended to stimulate thought and debate by analysing some consequences of these developments. It reviews literature in relation to risk-taking in UK operational policing, identifying increased criminal and disciplinary liability, particularly in respect of alleged omissions. Hindsight is found to be a potentially powerful influence. The article concludes that it is unlikely that public culture will be changed readily. However, police and other bodies should be able to reach a common approach towards operational risk, omissions and hindsight.